Regulation of Electric Vehicles in Indonesia as an Attempt to Reduce Gas Emissions - Audrey Ramadhina; Fatma Ulfatun Najicha (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Vehicles are already attached to the human self and cannot be released. But motor vehicles also make a bad impact on humans. Along with the development of the times, electric vehicles were created that are environmentally friendly. Therefore, the Government supports the development of electric vehicles, by issuing several regulations and regulations. The research method that the author uses in this study is a normative juridical approach. The normative juridical approach is an approach that is carried out based on the main legal materials by examining theories, concepts, legal principles and laws and regulations related to this research. Keywords : Electric Vehicles, Regulation, Gas Emissions